Keefektifan Pembelajaran Holistik Integratif dalam Mengembangkan Keterampilan Sosial Anak Usia 4-6 Tahun di Taman Kanak-Kanak Fajar Desa Cintakarya Kecamatan Parigi Kabupaten Pangandaran - Raden Iyus Surya Drajati; Euis Robi’ah Adawiyah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
Integrative holistic learning is a process of forming students as a whole including education, aspects of health and nutrition of AUD, aspects of parenting, aspects of early detection of growth and development and aspects of protection. Children's social skills are forms of behavior, deeds and attitudes displayed by each individual to interact, associate, relate, with all existing norms and rules, so that they can accept and be accepted by the environment itself by benefiting. The form of skill is to be cooperative with friends, show empathy, express emotions reasonably, show a tolerant attitude, obey the rules of the game. This study aims to describe holistic integrative learning in developing social skills.This research is descriptive qualitative. Data were collected through observation, documentation, interviews and anlysis documents. The data is analyzed using data reduction, displaying data and taking conclusions. The results showed that the development of children's social skills through integrative holistic learning can be seen from changes in the development of children's social skills. Development is evolving from before. On the results of observations in the application of integrative holistic learning students experience developments in terms of being cooperative with friends, showing empathy, expressing emotions reasonably, showing a tolerant attitude, obeying the rules of play. This study aims to describe holistic integrative learning in developing social skills. Thus, integrative holistic learning is effective in developing social skills.